Sequencing the unsequenceable: Expanded CGG-repeat alleles of the fragile X gene - Loomis, Erick W.; Eid, John S.; Peluso, Paul; Yin, Jun; Hickey, Luke; Rank, David; McCalmon, Sarah; Hagerman, Randi J.; Tassone, Flora; Hagerman, Paul J.

(untitled) (Genome Research, 2013)
The human fragile X mental retardation 1 (FMR1) gene contains a (CGG)n trinucleotide repeat in its 5′ untranslated region (5′UTR). Expansions of this repeat result in a number of clinical disorders with distinct molecular pathologies, including fragile X syndrome (FXS; full mutation range, greater than 200 CGG repeats) and fragile X–associated tremor/ataxia syndrome (FXTAS; premutation range, 55–200 repeats). Study of these diseases has been limited by an inability to sequence expanded CGG repeats, particularly in the full mutation range, with existing DNA sequencing technologies. Single-molecule, real-time (SMRT) sequencing provides an approach to sequencing that is fundamentally different from other “next-generation” sequencing platforms, and is well suited for long, repetitive DNA sequences. We report the first sequence data for expanded CGG-repeat FMR1 alleles in the full mutation range that reveal the confounding effects of CGG-repeat tracts on both cloning and PCR. A unique feature of SMRT sequencing is its ability to yield real-time information on the rates of nucleoside addition by the tethered DNA polymerase; for the CGG-repeat alleles, we find a strand-specific effect of CGG-repeat DNA on the interpulse distance. This kinetic signature reveals a novel aspect of the repeat element; namely, that the particular G bias within the CGG/CCG-repeat element influences polymerase activity in a manner that extends beyond simple nearest-neighbor effects. These observations provide a baseline for future kinetic studies of repeat elements, as well as for studies of epigenetic and other chemical modifications thereof.